Branislav Nušić's columns as a forerunner of literary journalism in Serbian journalism - Domazet-Daničić Sanja (CM. Communication and Media, 2023)
This paper analyzes the specific features of Branislav Nušić's individual style, which are manifested in the discourse of "feljtons" (today we define those texts as columns), published in the daily newspaper "Politika", in the period from 1904 to 1907. The paper will use the methods of text analysis, as well as the literary and artistic style of writing, which will accentuate the special stylistic features of Nušić's newspaper texts, which are the forerunners of the contemporary Serbian column and literary journalism. The individual characteristics of Branislav Nušić's writing style (at the time of the creation and publication of the column, he signed himself as Ben Akiba), include the incorporation of the language and speech forms of the time into the columnist discourse, the use of literary and artistic style of writing, which indicates that Nušić's texts from "Politics" are the basis on which contemporary writers write columnists, and his functionalist style (where irony and sarcasm alternate, gradation, repetition of sentences, syntactic parallelism, and all in the spirit of creating a comic effect), made it possible for his newspaper texts, which abound in familiarisms, expressive tone, emotional expression, allegorical, with heteroglossicity, affectation and dramaturgical composition, they gained wide readership and public attention. The paper will show that Nušić's texts are linguistically and stylistically vital, thematically contemporary, with a convincing presentation, but also with satire and the ever-present metaphysical pessimism, where the eternal theme of power, kinship hypocrisy and double morality are mocked, distinctly modern and with the anticipatory ability of their author. Even though more than a century has passed since they were created, Nušić's columns are fabula nostra even today, exciting and topical in terms of theme, language and style, so this work will show that Nušić can rightly be called not only a playwright, diplomat, amateur photographer and pioneer rhetoric in us, but also a first-class journalist.